Separation and Determination of Sulfonamides by Microchip Electrophoresis with Laser-Induced Fluorescence - Chen, Fang-Yuan; Li, Peng; Wang, Yan-Hong; Lian, Hong-Zhen (Asian Journal of Chemistry, 2013)
A simple and sensitive microfluidic capillary electrophoresis method with laser induced fluorescence detection was developed for the analysis of sulfonamides using fluorescein isothiocyanate as derivatization reagent. The performance of the system was demonstrated through the separation and determination of sulfamethazine, sulfamerazine and sulfamethoxazole in a running buffer solution containing 20 mmol/L borax (pH 9.2) with 15 % (v/v) ethanol. The injection and separation voltages, the concentration of borax, pH of the buffer and the content of ethanol in running buffer were optimized to get great influence on the separation. This proposed method showed satisfactory sensitivity with the limits of detection (S/N = 3) of 0.01 to 0.04 μmol/L for the sulfonamides. The method also exhibited very good reproducibility with the relative standard deviations of not more than 9.2 and 2.2 % for fluorescence intensity and migration time, respectively. The analysis was achieved within only 1.6 min.